Measuring The Implementation Of Regulation Of The Minister Of Health Number 97 Of 2014 Concerning Delivery In Health Facilities - Andris Isa (Estudiante Law Journal, 2020)
This study aims to find out the implementation of Article 14 Paragraph 1 of the Regulation of Minister of Health Number 97 of 2014 regarding delivery in health care facilities in Tolangohula Sub-district, Gorontalo Regency. The type of research used in this study was empirical legal research, in this study, the sampling used purposive sampling and the data analysis used by researchers in legal research used descriptive analysis. The results showed that policy implementation failed because the content of the policy was still unclear, meaning that the objectives were not detailed enough, the means and application of priorities, or the policy programs were too general or did not exist at all. Second, because of the lack of internal and external provisions of the policies to be implemented. Third, the policies to be implemented may also show significant deficiencies. Fourth, other causes of failure to implement a public policy can occur due to deficiencies concerning auxiliary resources, for example, those concerning time, cost/funds, and human labor. Legal awareness of the local community, especially pregnant women, so that they can take advantage of the facilities provided by the government in the form of Public Health Center and Auxiliary Health Center and even the nearest hospital, this is to ensure the safety of mothers and children as well as reduce the risk of maternal and child mortality.Keywords: Delivery; Facility; Health